Establishment of Potassium Reference Values Using Bayesian Models in Grapevines - Tassinari, Adriele; Dos Santos, Eduardo Maciel Haitzmann [UNESP]; Stefanello, Lincon Oliveira; Vitto, Beatriz Baticini; de Siqueira, Gustavo Nogara; Schwalbert, Raí Augusto; Ceretta, Carlos Alberto; Schwalbert, Raissa; Tiecher, Tadeu Luis; Ciotta, Marlise Nara; Hindersmann, Jacson; de Oliveira, Filipe Nunes; et al. (MDPI, 2022)
Critical levels (CL) of available potassium (K) in soils and leaves and maximum technical efficiency (MTE) doses are relevant information to define the best K fertilization strategies. The aim of this study was to determine reference values of K in leaves and soil, using Bayesian analysis, in order to maximize grape yield and must quality of ‘Chardonnay’ and ‘Pinot Noir’ grown in a subtropical climate. The vines were subjected to applications of 0, 20, 40, 60 and 80 kg K2O ha−1 year−1. The CL and MTE doses of K, in leaves and soils, were determined using Bayesian hierarchical models. The range of probability of the occurrence of CL in leaves was 15.8 to 18.9 g K kg−1 in ‘Chardonnay’ and 16.8 to 19.1 g K kg−1 in ‘Pinot Noir’ at flowering. Moreover, the range was 15.3 to 18.1 g K kg−1 in ‘Chardonnay’ and 16.1 to 18.2 g K kg−1 in ‘Pinot Noir’ at veraison. In the soil, the CL of available K for ‘Chardonnay’ was 27.4 mg K kg−1 and for ‘Pinot Noir’ it was 23.2 mg K kg−1. The increase of K in leaves and soil increased the TSS, while the TTA decreased in both cultivars after sufficiency rate. The MTE was estimated in ‘Pinot Noir’. The proposition of CL and/or MTE doses of K can help increase the efficiency of K fertilization in vineyards.
Keywords: grape chemical composition; grape yield; potassium fertilization; sustainable vineyard management; Vitis vinifera L